2020
DOI: 10.3390/ijerph17041203
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Benefits Equity of the Medical Security Policy: the China Health and Nutrition Survey (CHNS)

Abstract: Background: One of the fundamental objectives of the basic medical security system is to provide institutional guarantees for the appropriate medical needs of different groups. Among them, achieving fairness of benefits is the first principle of the system. This study aims to explore the benefit equity of preventive health care for different groups and the specific path to promote fairness. Methods: Based on the 2015 CHNS survey data, through the theory construction of benefit fairness in the basic medical ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This result is in line with a Canadian study that showed that area variation is the most important source of income-related health inequality, with income-related inequities in outpatient visits being mostly driven by differences between cities [48]. The cities in eastern and central regions have better health spatial accessibility, while in the western regions there is more limited spatial accessibility [49]. Moreover, this imbalance in outpatient visits can also be explained by different levels of medical resources and health insurance policies in different cities of residence [40].…”
Section: Discussionsupporting
confidence: 90%
“…This result is in line with a Canadian study that showed that area variation is the most important source of income-related health inequality, with income-related inequities in outpatient visits being mostly driven by differences between cities [48]. The cities in eastern and central regions have better health spatial accessibility, while in the western regions there is more limited spatial accessibility [49]. Moreover, this imbalance in outpatient visits can also be explained by different levels of medical resources and health insurance policies in different cities of residence [40].…”
Section: Discussionsupporting
confidence: 90%
“… 38 Nevertheless, compared to urban patients, lower overall PCC scores indicated that rural inpatients have greater dissatisfaction with medical services. Second, compared to the medical insurance schemes for urban patients, in recent years, the Chinese government has increased the reimbursement rate for patients who are covered by the NCMS 39 ; thus, rural residents’ disease burden has been significantly reduced. 40 This key development strategy has greatly improved rural patients’ expectations, as stated by most participants in our study, who reported that they can access medical services more conveniently and at affordable rates.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al (11) also found that lower-income groups benefited less than higher-income groups in China's URBMI program (11). Liu and Dai (2020) observed that compared to the highest-income group, below-middle-income groups had significantly insufficient compensation in China's basic medical insurance system (18). However, some gaps remain in existing studies.…”
Section: Introductionmentioning
confidence: 99%